Diffraction Efficiency In Case Of Small-Angle for Bragg Diffraction - Kadhim, Haider (University of Thi-Qar Journal of Science, 2010)
The diffraction efficiency of small- angle Bragg diffraction for three crystals different properties (KRS5, PbMo02, and LiNb03) has been investigated, respectively. The results have shown that, the change in the magnitude of diffraction efficiency by acoustic intensity (I acoustic) depends on the properties of the crystal used, especially, the relative figure of merit of the material ( Mw ). The maximum values of diffraction efficiency in case of the three crystals (KRS5, PbMo02, and LiNb03) have exactly been obtained at acoustic intensity (Iacoustic ) of values (Iacoustic = 0.7, 5, 100) respectively. So it has been possible to control diffraction efficiency by the intensity of acoustic wave (Iacoustic ).